Revealing Community Awareness in Semarang Heritage Area - Dewi, Santy Paulla; Debby, Tiara Rizkyvea (Jurnal Teknik Sipil dan Perencanaan, 2019)
The China Town Area is one of the historic areas that influenced the formation process of the Semarang City since the 17th century. However, in its development, there are several issues which are challenging in preserving the China Town as a cultural heritage area. Public awareness is one of the issues that arise in the heritage preservation effort.. Public awareness is formed based on knowledge that affects the community’s role of in the preservation. This research reveals the level of community awareness of the China Town Semarang towards the preservation of the Cultural Heritage Area. Qualitative research method was used to explain existing situation of community awareness. Interview was conducted with several key persons, for instance the Lurah, the owner of the Cultural Heritage Building, handicraft owners, and local community to find out the characteristics and their role in the preservation. Based on the analysis, it is found several issues exist suc as population number that decreases, high level of community migration, and buildings facade change. These issues affect the social conditions of the community, especially the understanding and awareness of the local community regarding the conservation of the China Town area as a Cultural Heritage Area. The factor of trust and upholding the customary principles is the background of the China Town community still maintaining its ancestral heritage.